If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + -5(-2) = 15 Multiply -5 * -2 1x + 10 = 15 Reorder the terms: 10 + 1x = 15 Solving 10 + 1x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 1x = 15 + -10 Combine like terms: 10 + -10 = 0 0 + 1x = 15 + -10 1x = 15 + -10 Combine like terms: 15 + -10 = 5 1x = 5 Divide each side by '1'. x = 5 Simplifying x = 5
| (z-2000)/5000=0.375 | | z-2000/5000=0.375 | | (m-n)-(6m+7n)= | | (5x-7y)-(5x+7y)= | | 3(2)+2(-3)= | | (6x)^(5/2)-(3x)^(3/2) | | 3x^2-36x=-80 | | -3(x-1)-2x=4(x+4)+4 | | (5x-7y)-(5x-7y)= | | 4x^2+8x+80=6x^2-4x | | 7-4x=8x+5 | | x*3-7x+4=0 | | 0.09x^2-30x+600=0 | | 100+5+5x=180 | | 15-m=24 | | 3x+42+90=180 | | (2.5-z)/(2.5-1)=0.06 | | (x+y)+(x+y)+(x+y)= | | (10+11*-1)+3(4*-1+3)= | | (10+11*-1)+3(4*-1+3)=2 | | -4.6y-2(2.2y-7.2)=-2.1(y-20) | | 5y-1-3y=5.20 | | 7y(2x-5y)= | | (7a+7b)+(6a-8b)= | | x+3-2x=5+2x-3x | | 5-5x-2x=4 | | -10=25+3x | | 2x+3n+7=-43 | | (2a+5b)+(5a+2b)+(6a-8b)= | | 4910x+10=24 | | (2a+5b)+(5a+2b)= | | Ln(y)=5x+c |